Regional effect on meat quality traits of Buffalos in Bangladesh - Hasan, M; Chakrabartty, S; Rahman, MA; Akter, S; Murshed, HM; Azad, MAK (Meat Research, 2022)
The study was aimed to determine the management practices of buffaloes and the meat quality test at different villages of Pauba upazilla in Rajshahi, Madargonj upazilla in Jamalpur and sadar upazilla in Mymensingh district of Bangladesh. Total 15 respondents were randomly selected from three villages; each village consists of variable numbers of respondents. The period of data collection was from February to April, 2016. The data were collected through personal interview from the individual respondent present in their own house. Only buffalo rearing was the major occupation of the farmers followed by agricultural crop production. Most of them (70.0%) kept their buffaloes on their own land; but some of them (30.0%) kept buffaloes on a hired place. The farmers (60.0%) basically have no training skill for buffalo rearing but some of them have influences from the buffalo farmers (40.0%). Most of the buffalo farmers purchased one pair of buffalo at a time and reared buffalos for at least 2 years. They fed their buffaloes with locally available roughages and tree leaves which contained more crude protein (CP) and less crude fibre (CF). In time of autumn season, they send their buffalo in Sunamgonj or Sylhet region for proper feeding. Buffalo farmers mainly maintain semi-intensive feeding system. The major diseases of buffaloes in those areas were Foot and Mouth Disease, anthrax and black quarter. Most of them performed vaccination collected from the local market and they also practiced medication and deworming. The farmers were satisfied with the marketing facilities. In case of meat quality parameters with proximate analysis and the results indicate that the better management gives us better quality of meat. It can be suggested that, management practice is very important fact in our country to get good quality of meat. So, we should improve our management practice through scientific approach.